2016
DOI: 10.14507/epaa.24.2522
|View full text |Cite
|
Sign up to set email alerts
|

The impact of teacher attitudes and beliefs about large-scale assessment on the use of provincial data for instructional change

Abstract: Abstract:In the quest to improve measured educational outcomes national governments across the The Organisation for Economic Co-operation and Development (OECD) and beyond have instituted large-scale assessment (LSA) policies in their public schools. Controversy almost universally follows the implementation of such testing, related to such topics as: a) the uncertain quality of the tests themselves as psychometrics measures; b) the uses to which the data can and should be put; c) the unintended consequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…There were several themes from the literature examined: test design and data; teacher attitudes; supports for data use; and policy incentives. Each of these is treated separately in one paper in a series from the author (Copp, 2016a(Copp, , 2016b(Copp, , 2017. The complete survey is shown in Appendix 2 alongside the values assigned to different responses for analysis.…”
Section: Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…There were several themes from the literature examined: test design and data; teacher attitudes; supports for data use; and policy incentives. Each of these is treated separately in one paper in a series from the author (Copp, 2016a(Copp, , 2016b(Copp, , 2017. The complete survey is shown in Appendix 2 alongside the values assigned to different responses for analysis.…”
Section: Surveysmentioning
confidence: 99%
“…Coefficients are from multivariate regressions for the nationwide dataset, which allows one to see which scale variables had the most significant effects on different types of reactivity. For detailed analysis of lines of inquiry other than incentives, see Copp (2016aCopp ( , 2016bCopp ( , 2017. The variables with the greatest correlation with TTC, based on beta scores, are the attitudes variables (Copp, 2016a).…”
Section: Findings Four Lines Of Inquirymentioning
confidence: 99%
See 1 more Smart Citation
“…However, one of the most important deficiencies of large-scale testing remains the difficulty teachers often experience in utilizing these measures to help inform their future pedagogical practice (Copp, 2015; Volante and Cherubini, 2010).…”
Section: The Road Ahead For Education Governance In the Eumentioning
confidence: 99%
“…The study further discovered that teachers' attitudes had a significant and positive relationship with assessment data use, suggesting that teachers with a positive disposition toward the utility and value of certain types of data were more likely to use those data to inform their own instructional practices. Copp (2016) investigated teacher perception and use of assessment data for instructional purposes. After taken survey responses from 1963 Canadian teachers, results showed that teachers had good conception about assessment data and indicated that, they use often to alter classroom instruction.…”
Section: Introductionmentioning
confidence: 99%